THE MORAL CONSCIOUSNESS DYNAMICS OF STUDENTS IS THE POSITION IN THE PROCESS OF HIGH EDUCATION (World Bulletin of Social Sciences, 2024)
The development of people’s responsible relation to nature consists of the main content ant subject of ecologic component in moral behavior